Population dynamics of Rodents and Insectivores in lowland tropical rainforest ecosystem of Okomu National Park, Edo State, Nigeria - MI Omogbeme; CO Oko (Journal of Applied Sciences and Environmental Management, 2018)
The community structure of rodents and insectivores in the lowland tropical rainforest of Okomu National Park, Edo State, Nigeria was assessed using a combination of live-trapping and sighting techniques during the dry and wet seasons. Seventeen species (14 species of rodent, 3 species of insectivores) were captured, and 3 species (all rodents) were recorded as observed species. Of the total 737 individuals trapped, 680 individuals (92.3%) were rodents and 57 individuals (7.7%) were insectivores, with 185 individuals recaptured. The abundance of rodents and insectivores was significantly higher during the dry season than the wet season (p < 0.01). The Tullberg's softfurred mouse (Praomys tullbergi) was the most abundant species constituting 17.8% of the total number of captures, with the recapture of 38 individuals. The age composition of all captured small mammals varied significantly and between seasons. There was no significant difference in sex ratio for both seasons, however, males had higher capture frequency. This study suggests that seasonality tends to influence abundance and age structure of these small mammals, with no significant effect on their sex ratio. The rodent and insectivore species inhabiting the study area have a stable and thriving community, except for Atelerix albiventris.